Enhancement of Catalytic Activity and Selectivity for the Gaseous Electroreduction of CO2 to CO: Guidelines for the Selection of Carbon Supports. (15th September 2021) - Lim, Chulwan; Lee, Woong Hee; Won, Jong Ho; Ko, Young‐Jin; Kim, Sangkuk; Min, Byoung Koun; Lee, Kwan‐Young; Jung, Won Suk; Oh, Hyung‐Suk
Abstract: To secure the economic feasibility of electrochemical carbon dioxide reduction reaction (CO2 RR), a method of using support materials to reduce the amount of catalyst loading and increase catalytic activity for CO2 RR can be a solution. Herein, guidelines for selecting carbon support materials suitable for CO2 RR are reported. In a gaseous CO2 ‐fed CO2 RR electrolyzer, an Ag nanoparticle‐composited carbon nanocage (denoted as Ag/CNC) electrode exhibits an optimal performance for CO2 RR with a partial current density of ≈400 mA cm −2 . Ag/CNC showcases a uniformly dispersed morphology with Ag nanoparticles and sufficient hydrophobicity after the reaction to prevent flooding, which is known to inhibit the mass transfer of CO2 . Furthermore, the CNCs possess small amounts of carbon defects; this suppresses the catalytic activity for the hydrogen evolution reaction (HER), which is a side reaction of CO2 RR. Results of a three‐stack cell experiment with the Ag/CNC electrode reveal the possibility of a support‐based strategy for achieving an industrial‐level scaling of CO2 RR. This study suggests that the support material for CO2 RR should be considered not only on the basis of the morphology of carbon, uniform dispersion of Ag nanoparticles, and hydrophobicity of the electrode but also factors influencing the HER, such as carbon defects. Abstract : The guidelines are provided for selecting suitable carbon support to increase the catalytic activity and stability for the CO2 reduction reaction. This study reveals that the support material should be considered not only morphology of carbon, uniform dispersion of Ag nanoparticles, and hydrophobicity of the electrode, but also factors influencing the hydrogen evolution reaction, such as carbon defects.